A Novel, Blocking, Fc‐Silent Anti‐CD40 Monoclonal Antibody Prolongs Nonhuman Primate Renal Allograft Survival in the Absence of B Cell Depletion. Issue 11 (2nd July 2015) - Cordoba, F.; Wieczorek, G.; Audet, M.; Roth, L.; Schneider, M. A.; Kunkler, A.; Stuber, N.; Erard, M.; Ceci, M.; Baumgartner, R.; Apolloni, R.; Cattini, A.; et al.
<x xml:space="preserve">Abstract</x> CD40–CD154 pathway blockade prolongs renal allograft survival in nonhuman primates (NHPs). However, antibodies targeting CD154 were associated with an increased incidence of thromboembolic complications. Antibodies targeting CD40 prolong renal allograft survival in NHPs without thromboembolic events but with accompanying B cell depletion, raising the question of the relative contribution of B cell depletion to the efficacy of anti‐CD40 blockade. Here, we investigated whether fully silencing Fc effector functions of an anti‐CD40 antibody can still promote graft survival. The parent anti‐CD40 monoclonal antibody HCD122 prolonged allograft survival in MHC‐mismatched cynomolgus monkey renal allograft transplantation (52, 22, and 24 days) with accompanying B cell depletion. Fc‐silencing yielded CFZ533, an antibody incapable of B cell depletion but still able to potently inhibit CD40 pathway activation. CFZ533 prolonged allograft survival and function up to a defined protocol endpoint of 98–100 days (100, 100, 100, 98, and 76 days) in the absence of B cell depletion and preservation of good histological graft morphology. CFZ533 was well‐tolerated, with no evidence of thromboembolic events or CD40 pathway activation and suppressed a gene signature associated with acute rejection. Thus, use of the Fc‐silent anti‐CD40 antibody CFZ533 appears to be an attractive approach for preventing solid organ transplant rejection.